‘THEY CALL US KILLERS’: AN EXPLORATION OF HERBAL, SPIRITUAL AND WESTERN MEDICAL PRACTICES IN MOMBASA, KENYA - Enumah, Z. O.; Rafiq, Mohamed Y.; Ayele, Wossen (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: This paper attempts to describe the multi-dimensional perceptions of mganga/waganga (Kiswahili: traditional healers) by members of their constituencies, patients, government health officials and religious leaders in Mombasa, Kenya. It also seeks to investigate how these conceptions and perceptions influence the relationships between traditional healers and other stakeholders in the delivery of public healthcare services in Mombasa. Materials and Methods: A qualitative approach consisting of in-depth interviews and focus group discussions was employed and 43 research participants were interviewed during the period of two months in the summer of 2010. Data were recorded (video and audio), transcribed, and analyzed using the constant comparison method. Results: Findings indicate that varied opinions and interpretations of mganga influence both the decision-making process of the patient and the provision of healthcare by the healer. High tensions exist between mganga and other actors, and furthermore, such perceptions seem to evidence themselves in the government’s support for waganga, as well as the delineation of healthcare services—whereby certain stakeholders and participants are relegated to specific tasks. Conclusions: This research builds upon the growing body of knowledge on how African patients—in general and Kenya in particular—and healers inhabit a multifaceted arena of healing in order to effectively negotiate their positions and needs to make complex decisions involving care, contingent upon local economic, social, cultural, and religious factors.